A mútua implicação de uma nova semântica e uma nova ontologia: a forma de Lorenz B. Puntel superar os problemas ontológicos precedentes - Guerra, Jean Brás (2024)
The ontological debate is, without a doubt, one of the oldest themes in the history of philosophy, having its beginnings still in ancient philosophy, from the search for understanding what things are, and in view of this, formulated theories to better explain what would be the being as being, this question being the center of ancient and medieval philosophical thought. The substantialist theory initiated by Aristotle was one of the ways of interpreting the being, being practically hegemonic since this period, showing a duo-categorial vision in which the world is understood through two fundamental categories: the substratum (thing) and the attributes (properties and relations). Despite being predominant, such a theory has been criticized throughout its history, being even more questioned within contemporary philosophy, which led theorists to search for alternative ontological models, arising, among other theories, the bundle theory and the tropos theory, which have also not been immune to criticism. At the same time, contemporary philosophy has a challenging context, which is that it is situated after two turns that changed the way of philosophizing: the Copernican turn, fruit of kantian transcendental philosophy, and the contemporary linguistic turn. It is within this context that the systematic-structural philosophy of Lorenz B. Puntel, who aims at the articulation of a more coherent, sophisticated and comprehensive theoretical framework, also seeking to elaborate a new ontology that is free from the problems of the previous theories, which is the ontology of prime facts. One of the fundamental theses of the thought proposed here, is that from the centrality of language that the theoretical framework here possesses, semantics and ontology are understood as two sides of the same medal, and therefore, it is not enough to elaborate a new ontological theory if a new semantics is not also developed. Eschewing the compositional semantics implied by substantialist ontology, Puntel makes use of a strong version of the context principle from which the new semantics and the new ontology are articulated. As a concluding dimension of this new semantic-ontological thought, truth has a very relevant role, since it has both a character of determination, which refutes the basic thesis of deflationism that truth has only a character of redundancy, and also points to a formulation of a thesis of identity between a true prime proposition and a prime fact in the world, and therefore justifies semantics and ontology being the two sides of the same medal. The purpose of what will be proposed here, therefore, is not only to present the puntelian vision, but also to show how this thought takes into consideration the great challenges that are posed to a philosophical theory in the contemporary thought scenario, approaching ontological themes with the help of other authors, aiming to understand how it not only fits into this context, but also postulates a greater coherence in relation to other theoretical frameworks.